2021
DOI: 10.3991/ijet.v16i09.19653
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Reality (VR) in Teaching Students with Dyslexia

Abstract: Studies show that the number of dyslexic students is increasing, as it does the need of the appropriate learning techniques and methodologies increases as well. For the students with learning disability, generally and the dyslexic stu-dents specifically there aren’t enough technologies that helps them in the learning process. Not only the students with learning disability face this prob-lem but parents and teachers are involved as well. The challenge that students with dyslexia face is that they find difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
0
11
0
4
Order By: Relevance
“…Making a variety of innovative proposals for users with dyslexia is a great contribution, since the simulation allows those involved to give their respective opinions on the proposal until bringing it to its development, therefore the design of augmented reality in education contributes to student learning to such an extent that it fulfills its objective of including students with dyslexia and improving their participation with the use of these technologies [17] [18]. Augmented reality is one of the most effective techniques for education and entertainment, as well as to give motivation to their students in their learning process, so this research shows that students with dyslexia use the application with augmented reality to follow the letters in such a way that they are pronounced by the students [19].…”
Section: Literature Reviewmentioning
confidence: 83%
“…Making a variety of innovative proposals for users with dyslexia is a great contribution, since the simulation allows those involved to give their respective opinions on the proposal until bringing it to its development, therefore the design of augmented reality in education contributes to student learning to such an extent that it fulfills its objective of including students with dyslexia and improving their participation with the use of these technologies [17] [18]. Augmented reality is one of the most effective techniques for education and entertainment, as well as to give motivation to their students in their learning process, so this research shows that students with dyslexia use the application with augmented reality to follow the letters in such a way that they are pronounced by the students [19].…”
Section: Literature Reviewmentioning
confidence: 83%
“…Prior studies have developed some applications to improve learning proficiency in (a) reading skills (Dyslexia Baca, DytectiveU, EasyLexia, Namagi, Alphabetics, AlphaTots), (b) mathematics (Talasia, Calculic Kids, MathFun, Coolmath4kids), or (c) both (Cognifit, Starfall). Furthermore, alternative research has suggested additional technologies such as VR ( Hwang and Hu, 2013 ; Maskati et al, 2021 ; Rodríguez-Cano et al, 2021 ), AR ( Ho et al, 2011 ; Vinumol et al, 2013 ; Avila-Pesantez et al, 2019 ; Gupta et al, 2019 ; Tenemaza et al, 2019 ; Kellems et al, 2020 ; Miundy et al, 2020 ), and eye-tracking ( Katona, 2023 ) to enhance learning abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they tried to explore the usability of their framework in several discipline areas to provide students life-enriching experiences. Maskati et al [16] developed an VR application for students with learning disability. By tracing the Arabic letters, this VR application allows students with dyslexia to learn alphabet effectively.…”
Section: Related Workmentioning
confidence: 99%